Spherical and rod-shaped nanocellulose from filter paper waste: A comparative study of acid hydrolysis - Istiqomah, Zahrotul; Holilah; Prasetyoko, Didik; Sunarmi, Sri; Juwono, Hendro; Pratama, Agus Wedi; Rani, Mohd Saiful Asmal; Indriani, Dina Wahyu; Knight, Victor Feizal; Norrrahim, Mohd Nor Faiz (Elsevier B.V., 2026)
Filter paper waste represents a significant yet underutilized feedstock for producing nanocellulose, a high-value nanomaterial essential for bioplastics and nanocomposites due to its biodegradability and mechanical strength. Valorizing this laboratory byproduct supports circular economy principles by converting waste into functional materials. In this study, nanocellulose was successfully isolated from filter paper waste (FPW). Cellulose extracted from the FPW was converted into nanocrystalline cellulose (NCC) through acid hydrolysis using two inorganic acids (sulfuric and hydrochloric) and two organic acids (citric and formic). The results revealed that acid type significantly influences particle morphology: hydrolysis with inorganic acids yielded spherical NCC particles, while the organic acids produced thin rod-shaped NCC. The average particle diameters of NCC from sulfuric and hydrochloric acid were 42.08 nm and 53.14 nm, respectively. FPW-NCH exhibited the highest crystallinity (87.40%), while FPW-NCS showed the lowest thermal stability (degradation onset at 220 °C). These findings demonstrate that simple acid selection is a critical tool for tailoring nanocellulose properties for specific end-use requirements